Spatio-temporal analysis of shoreline changes and erosion risk assessment along Jerba island (Tunisia) based on remote-sensing data and geospatial tools - Boussetta, Amina; Niculescu, Simona; Bengoufa, Soumia; Zagrarni, Mohamed Faouzi (Regional studies in marine science, 2022)
Jerba, the largest island in North Africa, is among the most exposed islands to the combined effects of climate change and human activities in the Mediterranean. The eastern coast of Jerba island has long been subject to intense tourist development due to its attractive natural potential. The main issue addressed in this study concerns the evolutionary trends of Jerba shoreline and the assessment of coastal erosion risk. This work focuses on the historical study of the shoreline positions based on satellite data processing. The use of geographic information system (GIS) and the Digital Shoreline Analysis System (DSAS) geostatistical calculation tool allowed for the identification of erosion and accretion rates and the description of evolutionary trends across 32 years covering three periods (1989–1999, 1999–2009, and 2009–2021). The results show an overall erosion trend (89% of the coastline). The statistics revealed that the study area, with the exception of the sandy spit, has experienced an intense and alarming level of erosion between 1989 and 1999, with an end point rate (EPR) equal to −4.12 m/year. This net rate continued to be negative in the period between 1999 and 2009, with an EPR of −0.5 m/year. Between 2009 and 2021, the net rate of shoreline change is marked by slight accretion, at an average of +1.4 m/year. The overall long-term trend shows the shoreline is eroding, with an average linear regression rate of −1.38 m/year for the whole period. This trend is due to a combination of the cumulative effects of sea-level rise and anthropogenic actions. Therefore, sustainable management strategies need to be implemented urgently by coastal managers to restore the sectors that are susceptible to further erosion.